Exploring Sports Content Consumption: A Psychological Comparison of Video and Aggregated Platforms in China - Ke Jiang; Wei Li; Yang Song (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In the era of the Internet and social networks, the diversity of sports news, particularly during events like the Tokyo Olympics, presents a dynamic area of study. This paper examines the influence of digital platforms on sports news diversity in China, evaluating how different levels of institutional penetration affect content variety. Using Simpson's diversity index, this study assesses content diversity across various platforms by analyzing nations' visibility, medals' coverage, and athletes' visibility. Principal Component Analysis (PCA) was employed to reduce dimensions and extract keywords from news content, aiding in the visualization of the reporting frameworks of diverse platforms. The analysis reveals that video platforms, characterized by lower institutional penetration, showcase greater diversity and broader coverage of diverse actors compared to aggregated sites. Despite this diversity, there remains a tendency towards a convergent news framework across platforms. The findings suggest that maintaining a balance between diversity and convergence might be strategically beneficial for enhancing the effectiveness of sports news dissemination in China’s digital landscape.